2018
DOI: 10.1039/c7nr07243k
|View full text |Cite
|
Sign up to set email alerts
|

Gateway state-mediated, long-range tunnelling in molecular wires

Abstract: a If the factors controlling the decay in single-molecule electrical conductance G with molecular length L could be understood and controlled, then this would be a significant step forward in the design of highconductance molecular wires. For a wide variety of molecules conducting by phase coherent tunnelling, conductance G decays with length following the relationship G = Ae . It is widely accepted that the attenuation coefficient β is determined by the position of the Fermi energy of the electrodes relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…Only in this limit is the conductance truly exponential in the length, and the gap exponent β is a property of the band structure of the long wire, i.e., independent of the contact arrangement. In their experimental work, Sangtarash et al (2018) observed in alkane wires with an extra aromatic center unit an approximately exponential decay GðNÞ ≈ e −β 0 N with an effective exponent β 0 that is considerably smaller than β. Sangtarash et al explained their observation by invoking in-gap (gateway) states. From our perspective one would expect the effective exponent β 0 to characterize a preasymptotic regime that crosses over into a steeper decay at larger N.…”
Section: Anchor Transparency and Gateway Statesmentioning
confidence: 99%
“…Only in this limit is the conductance truly exponential in the length, and the gap exponent β is a property of the band structure of the long wire, i.e., independent of the contact arrangement. In their experimental work, Sangtarash et al (2018) observed in alkane wires with an extra aromatic center unit an approximately exponential decay GðNÞ ≈ e −β 0 N with an effective exponent β 0 that is considerably smaller than β. Sangtarash et al explained their observation by invoking in-gap (gateway) states. From our perspective one would expect the effective exponent β 0 to characterize a preasymptotic regime that crosses over into a steeper decay at larger N.…”
Section: Anchor Transparency and Gateway Statesmentioning
confidence: 99%
“…where ε 1 and ε 2 are the energy levels coupled to each other by V d . If ε 1 (ε 2 ) is weakly bonded to the left (right) lead, the transmission coefficient T (E) could be obtained form equation 65 as [32,33]:…”
Section: ) Density Of States From Green's Functionmentioning
confidence: 99%
“…The X[Ph]X series has already been characterised in Au-molecule-Au junctions, and an unusually low value of b was experimentally determined. 21,22 This phenomenon was later ascribed to the presence of two orbitals located at the metal-sulfur interface of the molecular junction, which act as charge transport "gateways" that reduce the effect of molecular length on the overall conductance. 22 The effect was only observed in covalently-bonded molecular wires, where the thiol proton is lost upon chemisorption at the Au electrodes, with the formation of strong Au-S bonds.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 This phenomenon was later ascribed to the presence of two orbitals located at the metal-sulfur interface of the molecular junction, which act as charge transport "gateways" that reduce the effect of molecular length on the overall conductance. 22 The effect was only observed in covalently-bonded molecular wires, where the thiol proton is lost upon chemisorption at the Au electrodes, with the formation of strong Au-S bonds. In nGaAs-X[Ph]X-metal junctions, b was found again to be in good accordance with the value obtained employing the same molecular wires in Au-molecule-Au junctions, thus suggesting that the same "gateway" states are present at the semiconductor-molecule interface.…”
Section: Resultsmentioning
confidence: 99%